Design and fabrication of a new free and force vibration test rig - Muhammad Naim, Othman (2012)
This design and fabrication of a vibration test rig shows the combination of free and force vibration test rig. The objective of the project is to design and fabricate the combination of free and force vibration test rig. This report also describes about the free and force vibration experiment and their functionality. Design generation is shown and solid three dimensional structures modelling of the test rig was developed using Solidworks software. This report also explains the fabrication process that is needed for this project. Material that was being used in this project is aluminium. The problems encountered during completion of this project are also show in the report. An idea of improvement for the combination of test rig is also provided for further improvement of the test rig. The expected result for this project can solve the entire stated problem statement.